Kewenangan Lembaga Adat dalam Penyelesaian Sengketa Perdata Berbasis Komunitas - Erleni, Erleni (Disiplin : Majalah Civitas Akademika Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2025)
This study analyses the authority of customary institutions in community-based civil dispute resolution in Indonesia, with a focus on constitutional recognition and integration with the state judicial system. Using a normative and qualitative legal approach, this study explores legal bases such as Article 18B of the 1945 Constitution, the Village Law, and regional regulations that support the role of customary institutions as restorative mechanisms. Key findings show that customary institutions are effective in handling communal disputes such as customary land, customary inheritance, and family conflicts through deliberation and customary rituals, which emphasise the restoration of social harmony rather than an adversarial approach. However, challenges such as the heterogeneity of authority, overlap with formal law, and lack of documentation cause legal uncertainty. An analysis of the relationship with the state judicial system reveals the potential for hybrid synergy, in which customary decisions are recognised as non-litigation preliminaries, as seen in Constitutional Court decisions and court cases. This study recommends a national grand design to integrate legal pluralism in order to achieve inclusive substantive justice. Practical implications include strengthening regional regulations and inter-agency collaboration to reduce the burden on the formal judiciary.